Nanomechanical properties of the ZEP-520 electron beam resist film. (June 2021) - Pan, J.C.; Lang, F.C.; Zhao, X.P.; Hou, X.H.; Li, J.J.
Highlights: The thicknesses of the ZEP-520 resist are characterised using nanoindentation. The hardness and modulus for different thicknesses of the resist are investigated. The local area function method without the substrate effect is proposed. The reliability and validity of the local area function method are verified. Abstract: The ZEP-520 electron beam resist has been widely used in electron beam lithography and mask fabrication owing to its high resolution and good sensitivity. The stiffness and stability of the ZEP-520 resist are related to its mechanical properties, i.e., its hardness and elastic modulus. A higher hardness and elastic modulus can endow the ZEP-520 resist with higher stiffness, thereby allowing it to overcome the issue related to the collapse of the electron beam resist pattern. However, to date, only few studies have reported the mechanical properties of the ZEP-520 resist, and the relationship between the thickness of the ZEP-520 resist and its hardness and elastic modulus has not yet been determined. To obtain this information, in the present work, silicon is used as a substrate to analyse the hardness and elastic modulus of the ZEP-520 resist with different film thicknesses via nanoindentation. Additionally, a local area function method is proposed, through which the hardness of thin films can be conveniently and accurately obtained without being affected by the substrate effect. It is found that the true hardness increases with the decrease of the thickness of the ZEP-520 resist film; however, the true elastic modulus has no clear relationship with the film thickness. For a film thickness of 412 nm, the true hardness and elastic modulus of the ZEP-520 resist film are found to reach the maximum values of 0.52 and 11 GPa, respectively.